Qandeel-e-adab Qawaid-u-insha Book 6 - Saeed Maqsood (Lahore: Asian educational publishers, 2014)
To familiarize Urdu as the national language, simple and interesting activities have been organized. Care has been taken to ensure the ease of users whose mother tongue is not Urdu. To develop the comprehension skills according to Bloom$1 (Bs Taxonomy has been introduced in the proper sequence of remembering, understanding, applying, analyzing, evaluating, and creating. Starting from making small sentences in pre-primary to making simple couplets and then writing essays and and understanding Urdu grammatical terms in grade 6$1 (Bhas been made very simple and comprehensive. Includes stimulating students to write an account of an event, story writing, letters.s
Keywords: Urdu Grammar